2013
DOI: 10.1111/jnc.12511
|View full text |Cite
|
Sign up to set email alerts
|

Expression of astrocytic genes coding for proteins implicated in neural excitation and brain edema is altered after acute liver failure

Abstract: In vitro and in vivo studies have suggested that reduced astrocytic uptake of neuronally released glutamate, alterations in expression of glial fibrillary acidic protein (GFAP) and aquaporin-4 (AQP-4) contribute to brain edema in acute liver failure (ALF). However, there is no evidence to date to suggest that these alterations occur in patients with ALF. We analyzed the mRNA expression of excitatory amino acid transporters (EAAT-1, EAAT-2), GFAP, and AQP-4 in the cerebral cortex obtained at autopsy from eight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
29
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 53 publications
3
29
0
Order By: Relevance
“…Loss of EAAT-2 gene and protein expression was recently reported in autopsied brain tissue from patients with ALF resulting primarily from viral hepatitis. 3 Expression of a second glutamate transporter EAAT-1 was unchanged in this material.…”
Section: Astrocytesmentioning
confidence: 81%
See 2 more Smart Citations
“…Loss of EAAT-2 gene and protein expression was recently reported in autopsied brain tissue from patients with ALF resulting primarily from viral hepatitis. 3 Expression of a second glutamate transporter EAAT-1 was unchanged in this material.…”
Section: Astrocytesmentioning
confidence: 81%
“…27,28 Loss of GFAP expression was recently described in autopsied brain tissue samples from patients who died as a result primarily of brain herniation due to ALF. 3 The astrocyte membrane is home to a range of high affinity amino acid transporters that include transporters for glutamate (EAAT-2), glycine (GLYT-1) and glutamine (SNAT-3 and SNAT-5) Expression of genes coding for many of these proteins has been shown to be downregulated in brain extracts from animals with ALF due to ischemic liver failure. EAAT-2 is a cloned and well characterized high affinity transporter for glutamate that is located on the astrocyte membrane primarily in forebrain of mammals.…”
Section: Astrocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…Number of experimental studies, as well as the study of the autopsy material of patients with ALF demonstrated violation of the expression of several key astrocytic proteins: Aqp-4, GFAP (glial fibrillar acidic protein) [47], glutamine transporter SNAT5, glutamate transporters (GLT-1 (SLC1A2 -solute carrier family 1 member 2; EAAT2 -excitatory amino acid transporter-2)), glycine transporters (GLYT-1), glucose transporters (GLUT-1), peripheral type benzodiazepine receptors [48]. Thus, K. K. Thumburu et al in the study of the cerebral cortex of 8 patients died in ALF showed an increase in the level of Aqp-4 mRNA and Aqp-4 IHC expression in the region of astrocyte microvascular perivascular end-feet, as well as marked decrease in mRNA level and intermediate filament protein GFAP expression on the background of the brain tissue cytotoxic edema pattern.…”
Section: Introductionmentioning
confidence: 99%
“…HE is potentially reversible and emerges as the major complication of acute or chronic liver failure (ALF, CLF)[2]. RF Butterworth in his recent review[3] stressed that brain edema that accompanies ALF is the primarily cytotoxic phenomena, and moreover, this correlates with alterations in expression of genes coding for key astrocytic proteins[4]. …”
Section: Introductionmentioning
confidence: 99%